PENGARUH JOB EMBEDDEDNESS TERHADAP KEPUASAN PELANGGAN - Muhammad Deafridhininetri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
Using a new construct, Job Embeddedness (JE), from the business management literature,this study examines the effects of JE on Job Performace (JP) and Costumer Satisfaction (CS)at PT. Bayer Indonesia. Samples from the company at PT Bayer Indonesia were collected bymailing a questionnaire survey to those who agreed to participate.The results of this studyindicate that the following variables have a significant impact on Job Embeddedness Fit,Links, Sacrifice, Job Performance and Costumer Satisfaction.The study suggests that the PTBayer Indonesia can improve JP by influencing its JE, specifically, by developing fit, links andsacrifice. The study provided that it is necessary to pay more attention to the dimensions of JEas a key source for organizations to enhance the competitive advantage which is of primesignificance for JP and CS. JE is valuable for evaluating employee retention in PT BayerIndonesia. The study observes that there is a critical shortage of JE and that a greaterunderstanding of the factors that influence the JP, including fit, links and sacrifice, is of greatimportance. Therefore, this study is to examine the relationship between JE, JP and CS amongemployees at PT Bayer Indonesia.Keyword: Job Embeddedness, Job Performance and Costumer Satisfaction